Motivation outweighs ability in explaining European consumers' use of health claims. (June 2017) - Hung, Yung; Grunert, Klaus G.; Hoefkens, Christine; Hieke, Sophie; Verbeke, Wim
Highlights: European consumers are only moderately motivated and able to use health claims. Motivation matters much more than ability in determining health claim use. Interest in healthy eating and information need emerge as drivers of motivation. Health claim knowledge plays a minor role in shaping motivation and ability. Policy implications to stimulate health claim use are proposed. Abstract: Health claims promise health benefits beyond basic nutrition, but their impact on food choices is largely determined by consumers' motivation and ability to process these claims. This study investigates the role of consumers' motivation and ability to process health claims as well as attitudinal and cognitive determinants in explaining the use of health claims. Data were collected in Spring 2014 through a cross-sectional quantitative online survey with samples representative for age, gender and region in 10 European countries: United Kingdom, Germany, The Netherlands, Spain, Slovenia, Czech Republic, France, Denmark, Greece, and Lithuania (n = 5337). Structural equation modelling was used to simultaneously estimate the strength and direction of effects between motivation and ability to process, various determinants, and two components of health claim use. Motivation to process emerged as a key determinant of European consumers' use of health claims. Ability to process impacted claim use to a much smaller extent, but was strongly and positively influenced by the motivation to process. In order to be motivated, consumers are required to experience a need for health-related information, which in turn is driven by an interest in healthy eating. Participants with greater health claim-related knowledge tended to be more able but less motivated to process health claims. There were no substantial differences in the tested model between countries that had regulation for health claims prior to 2006 and those that did not, despite the considerable differences in their historical and current prevalence of health claims. Therefore, European food and nutrition policies and marketing strategies should focus on ways to improve consumers' motivation to process health claims by increasing their interest in healthy eating and need for health-related information.